Dataset to manuscript entitled "Non-fluorescent transient states of tyrosine - a basis for label-free protein conformation and interaction studies" submitted to Scientifc Reports - Bagheri, Niusha; Widengren, Jerker (Royal Institute of Technology, 2023)
This folder contains all raw data underlying the results presented in a manuscript, submitted to Scientifc Reports, and entitled:

Non-fluorescent transient states of tyrosine - a basis for label-free protein conformation and interaction studies

Authored by:

Niusha Bagheri 1, Hongjian Chen 1, Mihailo Rabasovic 2, Jerker Widengren 1,*

1    Royal Institute of Technology (KTH), Experimental Biomolecular Physics, Dept. Applied Physics, Albanova University Center 106 91 Stockholm, Sweden

2 Laboratory for Biophysics, Institute of Physics Belgrade, Pregrevica 11811080 Zemun-Belgrade, Serbia

* Corresponding author (jwideng@kth.se)

The data files are grouped into the different techniques used to generate them, and refer to the figures/tables in the manuscript where the extracted results are presented.

ABSTRACT

The amino acids tryptophan, tyrosine, and phenylalanine have been extensively used for different label-free protein studies, based on the intensity, lifetime, wavelength and/or polarization of their emitted fluorescence. Like most fluorescent organic molecules, these amino acids also tend to undergo transitions into dark meta-stable states, such as triplet and photo-radical states. While this may be perceived as a problem, these transitions are also highly environment-sensitive and can be used as an additional set of parameters, reflecting interactions, folding states, and immediate environments around the proteins. In this work, we applied the transient state monitoring (TRAST) technique, analyzing the average intensity of tyrosine emission under different excitation modulations, to characterize the photo physics of tyrosine for such readout purposes. By investigating how the dark state transitions of tyrosine varied with excitation intensity and solvent conditions we established a photophysical model for tyrosine. Next, we studied Calmodulin (containing two tyrosines), which upon calcium binding takes a more folded conformation. From these TRAST experiments, performed with 280nm time-modulated excitation, we show that tyrosine dark state transitions clearly change with the calmodulin conformation, and may thus represent a useful source of information for (label-free) analyses of protein conformations and interactions.
Keywords: Physical Sciences; Fysik